Flexor Tendon Injuries in the Hand: A UK Survey of Repair Techniques and Suture Materials—Are We Following the Evidence?. (18th March 2014) - Rudge, W. B. J.; James, M.
Abstract : Introduction . Injuries to the hand are common, and poor functional outcomes can have significant long-term consequences affecting both work and social activities. Good outcomes following flexor tendon lacerations in the hand are dependent on a sound surgical repair allowing early active mobilisation. Materials and Methods . We reviewed the literature regarding the choice of suture material and repair technique. We then carried out a nationwide postal survey of plastic surgery hand units to assess the level of compliance with the evidence. Results . Fifty-four units were surveyed. The response rate was 72%, with the most popular core suture being Prolene (64%) and the most popular technique being the Kessler repair (36%). Discussion . Current evidence advocates a multistrand repair using Ethibond. We found that the majority of units are not following the evidence. We suggest the use of evidence-based departmental guidelines to improve the practice and outcomes following these common injuries.